SIRKULASI KITAB AL-TUHFAH AL-MURSALAH ILA RUH AL-NABI: Studi Translokalitas dan Dampaknya terhadap Masyarakat Muslim Aceh - Daud Lintang; Kombang Tua Siregar; Randy Putra Alamsyah (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2025)
This article examines the circulation, transnationality, and contribution of Tuhfah al-Mursalah in Aceh, which played a significant role in the development of Sufism and the Islamization of Indonesia in the 17th century. This research adopts a descriptive-analytical library research method with a qualitative approach. This approach was chosen to explore the dissemination and contribution of Tuhfah al-Mursalah to the advancement of Muslims and intellectual and spiritual development in Indonesia. Indirectly, this research also uses a historical study approach. The findings in this study indicate that the teachings of the seven grades of being (martabat tujuh) have been known by Syamsuddin al-Sumtrani and the Acehnese since the year 1601. Historical indications show that the work has played a significant role in shaping the tradition of Sufism in the archipelago. The process of adaptation and contextualization of Tuhfah al-Mursalah in Aceh shows complex translocal dynamics. The existence of Sufism teachings simultaneously contributed to the emergence of local traditions, such as “adat bak po teumeureuhom, hukom bak syiah kuala” showing the relationship between adat and sharia law. This phrase shows how the Acehnese were able to combine local traditions with the Islamic faith, so that adat and Islamic law were considered as two sides of the same coin, rather than two different things. This process involved linguistic and cultural translation, in which the ideas of the book were adapted to local understandings and contexts. Acehnese scholars also reinterpreted its contents using terms and analogies relevant to local traditions and culture. The presence and teachings of the book also drew comments and criticism from several scholars. Nuruddin ar-Raniri was the most vocal critic of the book's teachings. He considered the teachings of Martabat Tujuh al-Sumatrani as heretical and heterodox.